Dopaminylation of histone H3 in ventral tegmental area regulates cocaine seeking - Lepack, Ashley E; Werner, Craig T; Stewart, Andrew F; Fulton, Sasha L; Zhong, Ping; Farrelly, Lorna A; Smith, Alexander C W; Ramakrishnan, Aarthi; Lyu, Yang; Bastle, Ryan M; Martin, Jennifer A; Mitra, Swarup; et al. (Science (American Association for the Advancement of Science), 2020)
Vulnerability to relapse during periods of attempted abstinence from cocaine use is hypothesized to result from the rewiring of brain reward circuitries, particularly ventral tegmental area (VTA) dopamine neurons. How cocaine exposures act on midbrain dopamine neurons to precipitate addiction-relevant changes in gene expression is unclear. We found that histone H3 glutamine 5 dopaminylation (H3Q5dop) plays a critical role in cocaine-induced transcriptional plasticity in the midbrain. Rats undergoing withdrawal from cocaine showed an accumulation of H3Q5dop in the VTA. By reducing H3Q5dop in the VTA during withdrawal, we reversed cocaine-mediated gene expression changes, attenuated dopamine release in the nucleus accumbens, and reduced cocaine-seeking behavior. These findings establish a neurotransmission-independent role for nuclear dopamine in relapse-related transcriptional plasticity in the VTA.